A Study on Virtue and Faults of Security in Cloud Computing - Singh, Nikhil Kumar; Singh, Ashutosh Kumar (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a web technology computing which requires large scale processing and computing. For this extensive processing, it requires security and protection in cloud computing for shareable configurable resources for on-demand access. This paper describes about the cloud computing merits and demerits of existing security and protection models in cloud computing